THE EFFECT OF CONTEXTUAL LEARNING MODELS AND LEARNING STYLES ON PKN LEARNING OUTCOMES FOR FIFTH GRADE STUDENTS AT SD NEGERI 157635 AEK DAKKA 2 BARUS, CENTRAL TAPANULI REGENCY - Dina Tania Ginting; Daulat Saragi; Naeklan Simbolon (SENSEI RESEARCH CENTER, 2022)
The implementation of learning will be successful by making improvement efforts through appropriate learning strategies so that it can assist students in improving learning outcomes. The purpose of this study was to determine: (1) differences in Civics learning outcomes of students who were taught using contextual learning models with conventional learning models, (2) differences in Civics learning outcomes of students who had visual, kinesthetic, and auditory learning styles, and (3) interaction between learning models and learning styles on student Civics learning outcomes. The population of this study was the fifth grade students of SD Negeri 157635 Aek Dakka 2 Barus, Central Tapanuli Regency with a total of 84 people. The sample of this study was determined by the class of SD Negeri 157635 Aek Dakka 2 Barus, Central Tapanuli Regency = 30 participating in contextual model learning and = 30 participating in learning using conventional models. The research instrument to measure learning outcomes used multiple-choice tests and questionnaires for learning styles. The data analysis technique used two-way ANOVA at a significance level of = 0.05. The findings of the study showed: (1) Civics learning outcomes of students in contextual classes were different from conventional classes, (2) Students' Civics learning outcomes had differences based on learning styles, (3) There was an interaction between learning strategies and learning styles in influencing student Civics learning outcomes